Neuropsychiatric symptoms correlated with functional trajectories among people living with Alzheimer's disease dementia and Lewy body dementia: Managing Dementia‐Related Behaviors. (7th December 2020) - Borda, Miguel German; Aarsland, Dag; Oppedal, Ketil; Giil, Lasse Melvær; Vik‐Mo, Audun Osland; Alves, Guido; Tovar, Diego; Gonzalez, Maria Camila; Brønnick, Kolbjørn
Abstract: Introduction: Functionality is one of the most important markers of wellbeing in older adults. People with dementia lose functionality mainly because of cognitive impairment. However, little has been outlined regarding the independent association of Neuropsychiatric symptoms (NPS) on functional decline in this population, especially in those diagnosed with Lewy body dementia (LBD). The aim of our work is to study the association of NPS at time of dementia diagnosis and 5‐year longitudinal course with the 5 years' trajectory of functional decline in people with Alzheimer´s disease (AD) and LBD. Methods: This is a secondary analysis of the Dementia Study of Western Norway (DemWest) including a total of 196 patients with newly diagnosed AD (n=111) and LBD (n=85). Baseline information on NPS was obtained using the Neuropsychiatric Inventory (NPI), and activities of daily living (ADL) was assessed yearly during five years using the rapid disability rating scale (RDRS). The longitudinal functional trajectories were analyzed using linear mixed modeling, adjusting by Age, cognition, sex and comorbidity. Results: Total NPI score at diagnosis was associated with functional decline for AD (Est 0.007 SE 0.002 p‐value 0.0014) but not for LBD (Est 0.002 SE 0.003 p‐value 0.4258). NPI score longitudinal course was associated with the functional decline trajectory in AD (Est 0.004 SE 0.001 p‐value 0.0002) and LBD (Est 0.005 SE 0.002 p‐value 0.0070). Conclusion: NPS independently predicted the rate of functional decline in people with AD and LBD despite their cognitive status. These results highlight the relevance of early detection and intervention of NPS, which may also reduce functional decline.